Virtual Instruments for the Circuit Analysis with Interactive Parameter Modification - Brenner, Eberhard Stefan (International Journal of Online and Biomedical Engineering (iJOE), 2006)
Abstractâ??The contribution presents the possibilities of LabVIEW in the special application as formula interpreter by using of the formula node. The main advantage is the immediate presentation of results in case of a parameter modification. The presentation of the time behaviour, the calculation of characteristic values and curves for typical examples of power electronics and control engineering are shown. Index Termsâ??Education; Formula Interpretation; LabVIEW; Power Electronics; Virtual Instruments